Sanksi Terhadap Penerima Fidusia Yang Tidak Menghapuskan Jaminan Fidusia Elektronik - Yama, I Putu Budi Arta; Udiana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 1 (2020)DO - 10.24843/AC.2020.v05.i01.p12, 2020)
The purpose of carrying out the elimination of related fiduciary guarantees so that objects that are used as fiduciary collateral objects with the debt fiduciary debt paid off, then the object can be re-registered the same fiduciary guarantee. In the regulations regarding Fiduciary Guarantees namely Law Number 42 of 1999 does not regulate sanctions against parties who are given the mandate by statutory regulations to abolish fiduciary guarantees. The purpose of this paper is to analyze the sanctions against those appointed by the laws and regulations that do not abolish electronic fiduciary guarantees and who can eliminate electronic fiduciary guarantees. This study applies a method which is normative legal research and the approach is the statutory approach. The result of this research is that the sanction given is civil sanction, in the form of a claim for compensation which refers to the provisions of Article 1365 of the Civil Code and the party that can carry out the removal of fiduciary guarantees ie is a fiduciary recipient either through his power of attorney or representative, the attorney referred to is a Notary Public.